ANALISIS PENGARUH LDR, NPL DAN CAR TERHADAP RISIKO LIKUIDITAS PADA BANK PERKREDITAN RAKYAT (BPR) DI SUMATERA BARAT - Yerismal Yerismal (Politeknik Negeri Bengkalis, 2018)
This research aims to analyze the effect of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) on Liquidity Risk. The data used in this research was obtained from the annual publication of financial statements by each Bank Of “Perkreditan Rakyat” (BPR) in West Sumatera in 2008-2012. The number of samples is all BPR in West Sumatera, as many as 10 banks by the period 2008-2012. The analysis technique is a statistical test regression method and hypothesis testing using the F test and t test, that had previously been tested in the classical assumption first. Research findings show that the variables LDR, NPL and CAR simultaneously affect on Liquidity Risk at 5% level of significant. LDR was negative significant affect on Liquidity Risk,NPL was negative significant affect on Liquidity Risk, and CAR was positive significant affect on Liquidity Risk. From this research, R2 value is 0,877, it shows that 87,7% of the dependent variable (Liquidity Risk) can be explained by the independent variable (LDR, NPL and CAR), the remaining 12,3% is explained by the other variables outside the equation.